2019
DOI: 10.1186/s42483-018-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

A glycine-rich protein MoGrp1 functions as a novel splicing factor to regulate fungal virulence and growth in Magnaporthe oryzae

Abstract: Glycine-rich proteins (GRPs) have diverse amino acid sequences and are involved in a variety of biological processes. The role of GRPs in plant pathogenic fungi has not been reported. In this study, we identified and functionally characterized a novel gene named MoGRP1 in Magnaporthe oryzae, which encodes a protein that has an N-terminal RNA recognition motif (RRM) and a C-terminal glycine-rich domain with four Arg-Gly-Gly (RGG) repeats. Deletion of MoGRP1 resulted in dramatic reductions in fungal virulence, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 70 publications
3
24
0
Order By: Relevance
“…To test whether this measurement works for secreted proteins, the fluorescence intensity of the P131 strain expressing control GFP alone was measured and the rate of secretion was calculated as 0.08, indicating that unfused GFP was not secreted into the liquid CM. Moreover, Slp1-GFP was secreted in the P131 strain at a rate of 0.36, while the nuclei-localized protein MoGRP1-GFP was secreted at a rate of 0.06, supporting the observation that Slp1-GFP but not MoGRP1-GFP was secreted into the liquid CM in the P131 strain [27] (Supplemental Fig. 2B).…”
Section: Resultssupporting
confidence: 72%
“…To test whether this measurement works for secreted proteins, the fluorescence intensity of the P131 strain expressing control GFP alone was measured and the rate of secretion was calculated as 0.08, indicating that unfused GFP was not secreted into the liquid CM. Moreover, Slp1-GFP was secreted in the P131 strain at a rate of 0.36, while the nuclei-localized protein MoGRP1-GFP was secreted at a rate of 0.06, supporting the observation that Slp1-GFP but not MoGRP1-GFP was secreted into the liquid CM in the P131 strain [27] (Supplemental Fig. 2B).…”
Section: Resultssupporting
confidence: 72%
“…The important roles of a few splicing factors in the growth, development, and virulence of rice pathogens have been identified in recent genetic and transcriptomic studies. For example, the auxiliary splicing factor gene MoGRP1 (encoding a glycine-rich protein) modulates growth, development, virulence, and stress responses in rice blast fungus [ 169 ]. MoGRP1 interacts with spliceosome components and plays a crucial role in modulating hyphal growth and conidiation by regulating the normal splicing of the corresponding genes, such as MST7 and MoRAD6 .…”
Section: Biotic Stressmentioning
confidence: 99%
“…MoGRP1 interacts with spliceosome components and plays a crucial role in modulating hyphal growth and conidiation by regulating the normal splicing of the corresponding genes, such as MST7 and MoRAD6 . Furthermore, besides their impaired mycelial growth, conidiation, and virulence, the Mogrp1 mutant fungi are unable to cause lesions on rice leaves [ 169 ]. Similarly, the silencing of SR gene NlSRp54 greatly decreases the survival of virulent BPH on resistant Mudgo rice, implicating an essential role of AS in the BPH-rice interaction and possibly in the rice resistance breakdown [ 158 ].…”
Section: Biotic Stressmentioning
confidence: 99%
“…Another study reported that Srk1 participates in the developmental stages of vegetative growth, sexual reproduction, and plant infection and is also required for pre‐mRNA AS and gene expression in F. graminearum (Wang et al ., ). MoGrp1, a novel splicing factor with poly(U)‐binding activity, plays a critical role in regulating fungal virulence, development, and stress responses (Gao et al ., ). These studies illustrate that posttranscriptional modification is required for fungal pathogenicity and development.…”
Section: Discussionmentioning
confidence: 97%